Hybrid stars within a covariant, nonlocal chiral quark model - Blaschke, David (2007)
We present a hybrid equation of state (EoS) for dense matter in which a nuclear matter phase is described within the Dirac-Brueckner-Hartree-Fock (DBHF) approach and a two-flavor quark matter phase is modelled according to a recently developed covariant, nonlocal chiral quark model. We show that modern observational constraints for compact star masses (M~2M⊙) can be satisfied when a small vector-like four quark interaction is taken into account. The corresponding isospin symmetric EoS is consistent with flow data analyses of heavy ion collisions and points to a deconfinement transition at about 0.55 fm⁻³.